The Continuing 'Wind of Change' in the Balkans: Sources of Housing Inequality in Bulgaria - Vesselinov, Elena (Urban Studies (Routledge), 2004)
The research in this paper explores the institutional changes in the housing system during the period of market transition in Bulgaria, which follow suit with the greater societal transformations. The societal changes are linked theoretically with Polanyi's understanding of the transition from a non-market to a market society. His argument helps in establishing the institutional context of the macroeconomic changes in the past decade. The article then focuses on the changing sources of housing inequality. It is argued that there are two urban regimes of housing inequality: the regime of controlled uniformity during the period of socialism and the regime of primitive diversity during the period of market transition. The two regimes are produced mainly through the changing role of the state.
Keywords: Bulgaria; cities & towns; equality; housing; macroeconomics; socialism; urban studies

Rules of Privatization: Contradictions in Neoliberal Regulation of North Pacific Fisheries - Mansfield, Becky (Annals of the Association of American Geographers, 2004)
Recent changes in fisheries regulation in the U.S. North Pacific reveal how neoliberalism is constituted in practice, and the forms that neoliberalism takes when it engages with environmental management and ecological processes. Whereas neoliberalism can be taken as a political economic philosophy that posits that markets, without state involvement, can best allocate resources, the history and practice of neoliberalism show that it is not as unified as it often appears. Analysis of contemporary fisheries policy reveals not only contradictions in neoliberal approaches, but also how those contradictions are shaped by the environmental context of the industry. This article discusses the rationale for neoliberalism in fisheries and the governance changes enacted in the 1998 American Fisheries Act, which privatized the fishery for Alaska pollock by closing the fishery to all new entrants, providing a set percentage of the yearly catch to “cooperatives” of participants, and allowing individuals to lease their shares. Karl Polanyi's notion of the “double movement” provides a framework to argue that even though regulators tout these reforms because they rely on market mechanisms to resolve recalcitrant ecological and economic problems in these fisheries, writing and implementing the act simultaneously involved complex rule making designed to protect the market. This form of neoliberalism results from the history of fisheries regulation, including recent emphasis on cooperative management, and the ecological characteristics of marine fish. Moves to privatize the oceans entail developing distinctive forms of neoliberal practice that uniquely combine private industry and government regulation. Because fish are one of the last great resource commons, neoliberal approaches to fisheries mark a profound geographical transformation in the political economy of the oceans.
Keywords: Pacific Ocean; double movement; fishery policy; neoliberalism; privatization

'Spatial' relationships? Towards a reconceptualization of embeddedness - Hess, Martin (Progress in Human Geography, 2004)
The concept of embeddedness has gained much prominence in economic geography over the last decade, as much work has been done on the social and organizational foundations of economic activities and regional development. Unlike the original conceptualizations, however, embeddedness is mostly conceived of as a 'spatial' concept related to the local and regional levels of analysis. By revisiting the early literature on embeddedness - in particular the seminal work of Karl Polanyi and Mark Granovetter - and critically engaging with what I will call an 'overterritorialized' concept, a different view on the fundamental categories of embeddedness is proposed. This reconceptualization then is illustrated using the poststructuralist metaphor of a rhizome to interpret the notion of embeddedness and its applicability to different geographical scales.
Keywords: GRANOVETTER, Mark; associations; cosmography; economic geography; embeddedness; geography; global production networks; institutions; new regionalism; organization; rhizome; social networks; socioeconomics